Hyperoxia exposure promotes endothelial–mesenchymal transition and inhibits regulatory T cell function in human pulmonary microvascular endothelial cells - Sun, Yifan; Yan, Chongbing; Liu, Yibo; Lin, Yating; Weng, Bowen; Gong, Xiaohui; Cai, Cheng (Frontiers in Pediatrics, 2024)
Objective: This study aims to investigate the effects of hyperoxia exposure on TGF-β1-induced endothelial-mesenchymal transition (EndoMT) and regulatory T cell (Treg) - mediated immunomodulation in human pulmonary microvascular endothelial cells (HPMECs), which could provide a theoretical basis for further studies of the pathogenesis of bronchopulmonary dysplasia (BPD). Methods: A BPD cell model was established by exposing HPMECs to hyperoxia. Flow cytometry was used to isolate CD4+CD3+CD25 +CD127- Tregs from the peripheral blood samples of preterm infants. HPMECs were divided into four groups based on whether they were exposed to hyperoxia and/or co-cultured with Tregs. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to test the expression levels of TGF-β1, α-SMA, Foxp3, IL-10, and reactive oxygen species (ROS). Results: The results showed that the expression levels of TGF-β1 and α-SMA in HPMECs increased at 24h, 48h, and 72h of hyperoxia exposure. In the co-culture group of HPMECs and Tregs, Foxp3 and IL-10 expressions decreased at 48h and 72h of hyperoxia exposure. ROS expression increased in the hyperoxia group of HPMECs at 24h, 48h, and 72h of hyperoxia exposure, which were higher than those in the hyperoxia group of HPMECs and Tregs. Conclusion: These findings suggest that hyperoxia exposure promotes EndoMT in HMPECs and inhibits the immunosuppressive effect of Tregs. Despite this, Tregs still seem could protect HPMECs from oxidative stress injury.